Development Assistance to Health Information Systems Strengthening - Boned-Ombuena, Ana (World Bank, Washington, DC, 2017)
The ultimate goal of Health, Nutrition and Population (HNP) interventions is to improve health outcomes in low, and middle-income countries. However, impact assessment requires the development of systems for effective monitoring and evaluation (M&E). As a consequence, there is increasing momentum toward supporting national health information systems (HISs) strengthening among development organizations. The new primary direction of the WB, as stated in the new HNP Strategy, is the renewed focus on HNP results. For this purpose, the WB intends to support the launch of a major effort to assist client countries to improve their national HISs. In preparation for implementing the Action Plan, the Performance Monitoring and Statistics Team (PMS Team) aims to identify and document the assistance that different development organizations have been providing in recent years to countries in order to improve their national HISs. The objectives of this report are: to compile an inventory of activities that development partners -including the WB, other UN agencies, bilateral development agencies, global health partnerships (GHP), and private foundations, have implemented in order to support the development of HISs in developing countries; and to review a sample of success stories in improving the capacity for collection of routine health information in developing countries.